2008
DOI: 10.1007/s00330-008-0971-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and tractography of the median nerve in carpal tunnel syndrome: preliminary results

Abstract: The purpose was to demonstrate the feasibility of in vivo diffusion tensor imaging (DTI) and tractography of the human median nerve with a 1.5-T MR scanner and to assess potential differences in diffusion between healthy volunteers and patients suffering from carpal tunnel syndrome. The median nerve was examined in 13 patients and 13 healthy volunteers with MR DTI and tractography using a 1.5-T MRI scanner with a dedicated wrist coil. T1-weighted images were performed for anatomical correlation. Mean fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
160
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 35 publications
9
160
1
4
Order By: Relevance
“…MR neurography by using DWI can clearly show lumbar nerve roots, and the mean ADC in nerve root entrapment with foraminal stenosis is higher than in intact nerve roots in approximately a 10-minute scan time by using MR imaging at 1.5 T. 20 The ADC map is limited because the tissue contrast between nerves and surrounding tissues is poor. 15 In this study, we have shown that DTI can clearly show tractograms of lumbar nerve roots and determine FA values of the nerve roots in patients and healthy volunteers in approximately a 5-minute scan time by using MR imaging at 3T.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…MR neurography by using DWI can clearly show lumbar nerve roots, and the mean ADC in nerve root entrapment with foraminal stenosis is higher than in intact nerve roots in approximately a 10-minute scan time by using MR imaging at 1.5 T. 20 The ADC map is limited because the tissue contrast between nerves and surrounding tissues is poor. 15 In this study, we have shown that DTI can clearly show tractograms of lumbar nerve roots and determine FA values of the nerve roots in patients and healthy volunteers in approximately a 5-minute scan time by using MR imaging at 3T.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, several studies have shown that DTI is useful for the evaluation and visualization of peripheral nerves 15 and the measurement of axon regeneration in rat 16 and mouse 17 sciatic nerves, demonstrating that a decrease in mean FA values was observed in injured nerves with demyelination. [15][16][17][18] Imaging of the spinal cord is challenging because of technical limitations such as the relatively small size of the cord, susceptibility artifacts because of tissue-bone interfaces, and the motion artifacts arising from respiratory activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the major white matter tracts of each subject were reconstructed in 3 sessions: 2 yielding the PF and 1 yielding the CF. Quantitative results of the generated fibers, including the right and left PF, CF, and the summation of these tracts (MWT), were automatically obtained by the software, 26 initiated by right-clicking with the mouse on the fibers. The results include the FA, NOP, and NOF.…”
Section: Roi Tractography Analysismentioning
confidence: 99%
“…DWI has been widely used for clinical applications in evaluation of the central nervous system for the diagnosis of diseases such as acute brain stroke [14]. Recently, it has been reported that DWI is useful for the evaluation and diagnosis of lesions such as multiple sclerosis [15,16] and peripheral nerve compression disorders such as carpal tunnel syndrome [17][18][19], using diffusion values such as ADC. An increase in the mean diffusivity (ADC) values was observed in injured nerves with demyelination [15,16,19,20].…”
Section: Introductionmentioning
confidence: 99%